Re-Circulatory Aquaculture Systems: A Pathway to Sustainable Fish Farming - Jham Lal; Anand Vaishnav; Suparna Deb; Shubham Kashyap; Payel Debbarma; Devati; Priyanka Gautam; Muneshwar Pavankalyan; Kriti Kumari; Durgesh Kumar Verma (Archives of Current Research International, 2024)
Recirculating Aquaculture Systems (RAS) represent a transformative approach to sustainable fish farming that offers a viable solution to meet the growing global demand for seafood while minimizing environmental impact. These closed-loop systems recirculate and reuse water, reducing water consumption by up to 99% compared to traditional aquaculture methods. RAS also mitigate the risk of disease transmission, escapement, and pollution by isolating farmed fish from natural populations and the surrounding environment. Technologically advanced RAS employ mechanical filtration, biological filtration, and disinfection processes to maintain optimal water quality for fish growth. This high level of control allows for the farming of a wide range of species, including predatory finfish, in locations far from coastal areas. Furthermore, the integration of aquaponics in RAS enables the production of high-quality vegetables and herbs using the nutrient-rich wastewater, creating a sustainable closed-loop system. Despite the higher initial investment required, RAS have demonstrated consistent profitability and the potential for significant returns. By promoting "in-sourcing" and creating local jobs, RAS can contribute to the economic development of communities while reducing the carbon footprint associated with international seafood trade. As the aquaculture industry continues to evolve, RAS are poised to play a crucial role in ensuring the long-term sustainability of fish farming. By combining technological advancements with environmental stewardship, RAS offer a promising pathway towards meeting the world’s growing demand for seafood while preserving the health of our aquatic ecosystems.